"Mirror, Mirror, on the Wall – Who Is the Greatest Investor of all?" Effects of Better‐than‐Average Beliefs on Venture Funding. Issue 2 (23rd August 2019) - Linder, Christian; Sperber, Sonja
Abstract : Agency theory considers information the most decisive element in investor–entrepreneur relations. Building on the notion of better‐than‐average (BTA) beliefs, we investigate the extent to which information asymmetries between investors and entrepreneurs may also emerge on paths other than the self‐interest or opportunistic behaviour of rational actors . Based on a data set of 176 investors from 23 different German financial institutions, we conduct a conditional process analysis that indicates approximately 30% of all professional investors hold unjustified BTA beliefs regarding their abilities to identify flaws in new venture ideas, which leads to inaccurate financing decisions . We further find evidence that investors generally tend to underfund start‐up projects if they perceive little similarity with the founders, but overfund projects if interpersonal similarities are high . Moreover, we demonstrate that high BTA beliefs facilitate engagement in competition with peers for the best investment option .